A RARE CASE OF PARATHYROID ADENOMA PRESENTING WITH HOARSENESS - Nunez, Noemi Angel; Ong-Ramos , Celeste (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE A 47-year-old Filipino male presented with hoarseness and aspiration episodes for 3 days. Transnasal endoscopy revealed right vocal cord paralysis. Neck MRI revealed an enhancing ovoid lesion measuring 0.9 x 0.9 x 1.8 cm in the posterior portion of the right thyroid lobe, with thickening and medial displacement of the right vocal cord consistent with right vocal cord paralysis secondary to a parathyroid adenoma. Workup showed elevated iCA 1.40 mmol/L (NV:1.09-1.30) intact PTH 160.10 pg/ml (NV:18.50-88) and low vitamin D 29.74 ng/ml (NV: 30-100). Creatinine was 1.22 mg/dl (NV: 0.55-1.02) with eGFR of 67.7 ml/min. SPECT/ CT revealed no sestamibi-avid parathyroid adenoma in the neck and mediastinum. Bone mineral densitometry was normal. He was managed as primary hyperparathyroidism secondary to parathyroid adenoma and underwent right lobectomy with parathyroidectomy. Histopathology showed an enlarged hypercellular parathyroid. He had a >50% decrease in iPTH (24.80 pg/ml), normal ionized calcium(1.25 mmol/L), and resolution of hoarsenes. He was discharged with vitamin D supplementation.